PENGARUH FASILITAS KANTOR MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DI KANTOR KECAMATAN RANGKUI KOTA PANGKALPINANG TAHUN 2021 - Nadiyah, Susi; Zamhari; Astuti, Nelly (Jurnal Progresif Manajemen Bisnis, 2021)
This an undergraduate thesis entitled in Bahasa Indonesia: “Pengaruh Fasilitas Kantor, Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Pegawai di Kantor Kecamatan Rangkui Kota Pangkalpinang". The purpose of this study was to determine the effect of office facilities, work motivation and work discipline in improving employee performance at the Rangkui sub-district office, Pangkalpinang City, both partially and simultaneously with 125 pages without attachments. Based on the supporting theories used in this research is the theory of human resource management (HRM), namely the theory of office facilities, the theory of work motivation, the theory of work discipline and the theory of employee performance. The method used in this study is to use a quantitative approach in the form of a questionnaire through a sample approach. Probability Sampling, is a sampling technique that provides equal opportunities for each element (member) of the population to be selected as a member of the sample. The sample in this study were employees at the Rangkui District Office, Pangkalpinang City, which amounted to around 30 employees. Simultaneously there is an Adjusted R2 value of 0.743 so the conclusion is that variable X, namely office facilities, work motivation and work discipline, can have an effect of 74.3% on variable Y, namely employee performance and the rest is 0.257 or equal to 25.7% performance. employees are influenced by other factors outside of this study. 1. Office facilities variable (X1) where t-count (3.960) > t-table (2.055) means that the office facilities variable (X1) has a partial effect on employee performance, meaning that H1 is accepted. 2. The work motivation variable (X2) where t-count (0.817) < t-table (2.055) means that the work motivation variable (X2) has no partial effect on employee performance, meaning that H0 is accepted. 3. The work discipline variable (X3) where t-count (3.067) > t-table (2.055) means that the work discipline variable (X3) has a partial effect on employee performance. it means that H1 is accepted. 4. The results of the F test are that a comparison of F-count 28.945 > F-table 2.98, it can be concluded that the variables of office facilities, work motivation and work discipline simultaneously affect employee performance variables, meaning that H1 is accepted. It can be concluded that office facilities, work motivation, and work discipline have an effect on simultaneously. However, partially, one of them has no effect on employee performance, namely work motivation at the Rangkui District Office, Pangkalpinang City.